Generation and Transmission Network Expansion Co-Planning Models: A Comprehensive Review - Chillogalli, José E. [UNESP] (2024)
In the realm of energy infrastructure planning, Generation Expansion Planning (GEP) stands as a critical component, aimed at determining the optimal generation unit capacities, resource combinations, locations, and commissioning schedules. In parallel, Transmission Network Expansion Planning (TNEP) is intended to identify the future requirements for transmission infrastructure, ensuring an efficient and reliable energy supply. While GEP and TNEP share a common goal of equipping generation and transmission networks to meet future demands, traditional approaches tend to address these aspects separately or sequentially, neglecting their inherent interdependence. To address this limitation, co-optimization models have been developed to integrate Generation and Transmission Network Expansion Planning (GTNEP) in a unified approach. In this work, a comprehensive review of the existing literature on GTNEP models is conducted. The objective of this review is to classify and identify gaps and opportunities for further research, spanning both centralized and liberalized electrical markets.